English Lecturers’ Perspectives on the English as a Lingua Franca (ELF) Paradigm in Teaching Practices: A Positive Outlook - Sastin o. Akase; Enni Ahkmad; Zulkifli Ahkmad; Andi Nurwati; Nur Wahidah Thayib Pido (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
The growing use of English in multilingual communication has strengthened the importance of English as a Lingua Franca (ELF) in English language teaching. Despite increasing international interest in ELF, empirical evidence on lecturers’ perspectives in regional Indonesian higher education institutions, particularly in Gorontalo, remains limited. This study aimed to investigate English lecturers’ perspectives toward the ELF paradigm in teaching practices at IAIN Sultan Amai Gorontalo and Universitas Negeri Gorontalo. A descriptive quantitative survey design was employed involving 26 English lecturers selected through purposive sampling. Data were collected using a validated 19-item questionnaire and analyzed using descriptive statistics, including mean scores, standard deviations, frequencies, and percentages. The findings revealed that lecturers generally demonstrated positive orientations toward the ELF paradigm. Four research dimensions—Legitimacy of All English Users, Rejection of Native-Speakerism Dominance, ELF as a Legitimate Form of Global Communication, and Diversity as a Strength in Communication—were categorized as high, whereas Emphasis on Imitating Native-Speaker Models and Dependence on Native-Based Teaching Materials remained at a moderate level. These findings indicate that lecturers are increasingly embracing multilingual and communication-oriented perspectives while still maintaining certain native-speaker-oriented beliefs, highlighting the transitional nature of lecturers’ perspectives toward ELF. The study contributes to the growing body of ELF and Global Englishes research by providing empirical evidence from an underrepresented Indonesian higher education context and demonstrates how global communicative principles are negotiated within local teaching practices. The findings also underscore the importance of integrating ELF-aware principles into curriculum development, teacher education, and professional development programs to better prepare learners for multilingual communication in contemporary English language teaching.